Beyond methylammonium lead iodide: prospects for the emergent field of ns2 containing solar absorbers. Issue 1 (6th October 2016) - Ganose, Alex M.; Savory, Christopher N.; Scanlon, David O.
Abstract : In this review we look beyond CH3 NH3 PbI3 to other ns 2 containing solar absorbers, with the aim of identifying those materials likely to achieve high efficiencies. Abstract : The field of photovoltaics is undergoing a surge of interest following the recent discovery of the lead hybrid perovskites as a remarkably efficient class of solar absorber. Of these, methylammonium lead iodide (MAPI) has garnered significant attention due to its record breaking efficiencies, however, there are growing concerns surrounding its long-term stability. Many of the excellent properties seen in hybrid perovskites are thought to derive from the 6s 2 electronic configuration of lead, a configuration seen in a range of post-transition metal compounds. In this review we look beyond MAPI to other n s 2 solar absorbers, with the aim of identifying those materials likely to achieve high efficiencies. The ideal properties essential to produce highly efficient solar cells are discussed and used as a framework to assess the broad range of compounds this field encompasses. Bringing together the lessons learned from this wide-ranging collection of materials will be essential as attention turns toward producing the next generation of solar absorbers.